Does the buck stop here? A comparison of withdrawals from money market mutual funds with floating and constant share prices - Jonathan Witmer (Bank of Canada, 2012)
Recent reform proposals call for an elimination of the constant net asset value (NAV) or buck in money market mutual funds to reduce the occurrence of runs. Outside the United States, there are several countries that have money market mutual funds with and without constant NAVs. Using daily data on individual fund flows from these countries, this paper evaluates whether the reliance on a constant NAV is associated with a higher frequency of sustained fund outflows. Preliminary evidence suggests that funds with a constant NAV are more likely to experience sustained outflows, even after controlling for country fixed effects and other factors. Moreover, these sustained outflows in constant NAV money market funds were more acute during the period of the run on the Reserve Primary fund, and were subdued after the U.S. Treasury guarantee program for money market funds was put in place. Consistent with the theory that constant NAV funds receive additional implicit support from fund sponsors, fund liquidations are less prevalent in funds with a constant NAV following periods of larger outflows.
Keywords: F30; G01; G18; G20; 330; Financial markets; Financial stability; Market structure and pricing